Development and Application of a New Convective Entrainment Rate Parameterization for Improving Precipitation Simulation Over the Tibetan Plateau and Its Surrounding Areas - Junjun Li; Chunsong Lu; Jinghua Chen; Jian Li; Jing Yang; Xiaoqi Xu; Lei Zhu; Xin He; Shiying Wu (Journal of Advances in Modeling Earth Systems)
Abstract The Tibetan Plateau (TP) significantly impacts the global climate. TP's unique geographical conditions make it one of the areas with the largest precipitation biases in numerical models. The overestimation and distribution biases of precipitation in models are closely related to the parameterization of convection processes over the TP. In light of this, a new deep convective entrainment rate parameterization suitable for the region is developed based on convection observational data and is applied to the Grell‐Freitas Ensemble Scheme of the Weather Research and Forecasting Model. The new scheme significantly reduces the overestimation of simulated precipitation over the TP, decreasing the overestimation from 29.4% in the default scheme to 11.8%. The physical mechanism behind the improved simulation results is as follows: first, the entrainment rate of convection in the new scheme is closer to the observed results. Second, in terms of cloud macrophysics, the new scheme increases the convective entrainment rate, reduces the cloud top height and depth of convective clouds, and decreases the number of grids with updrafts in the vertical layers and grids with convective precipitation on the surface. Third, in terms of cloud microphysics, the increased entrainment rate reduces the cloud water content and weakens the intensity of convective precipitation. All of these mechanisms ultimately reduce the accumulated convective precipitation amount, providing an optimized modeling tool for weather and climate research over TP, which also aids in better assessing the water cycle and water resource reserves of the “Asian Water Tower.”